«Філософія теперішнього» Дж. Г. Міда як онтологія процесу - Шамша, І. В.; Шамша, И. В.; Shamsha, I. V. (My University, 2017)
Статтю присвячено аналізу розуміння часу в концепції Дж. Г. Міда. Онтологія Дж. Г. Міда розуміється як онтологія процесу. Аналіз модусів часу приводить автора до висновку про те, що в концепції американського прагматика вічність виявляється протиставленою часу. Окрема увага приділяється поняттю емерджентності. На думку Дж. Г. Міда, саме емерджентність постає ключем до розуміння всіх модусів часу. Висловлюються думки про неприпустимість протиставлення будь-якого модусу (модусів) часу іншим модусам (або модусу), а також думки про неприпустимість зневажливого ставлення до будь-якого модусу часу чи його частин. Водночас з’ясовується, наскільки концепція часу Дж. Г. Міда наближає дослідника до цілісного розуміння часу, що дає змогу синтезувати сутність та існування людини.

Статья посвящена анализу понимания времени в концепции Дж. Г. Мида. Онтология Дж. Г. Мида понимается как онтология процесса. Анализ модусов времени приводит автора к выводу о том, что в концепции американского прагматика вечность оказывается противопоставленной времени. Отдельное внимание уделяется понятию эмерджентности. По мнению Дж. Г. Мида, именно эмерджентность является ключом к пониманию всех модусов времени. Высказываются мысли о недопустимости противопоставления любого модуса (модусов) времени другим модусам (или модусу), а также мысли о недопустимости уничижительного отношения к любому модусу времени или его частям. Вместе с тем выясняется, насколько концепция времени Дж. Г. Мида может приблизить исследователя к целостному пониманию времени, позволяющему синтезировать сущность и существование человека.

This article analyzes the understanding of time in the concept of the G.H. Mead. The G.H. Mead ontology is understood as the ontology of the process. Analysis of the modes of time leads the author to the conclusion that in the conception of the American pragmatist, eternity turns out to be opposed to time. Special attention is paid to the notion of emergence. According to G.H. Mead, it is emergence is the key to understanding all the modes of time. It was suggested about inadmissibility of opposition of modes of time with each other, and also the thought of inadmissibility derogatory attitude to any modus of time, or portions thereof. However, it is found out as far concept of the time of G.H. Mead can bring researchers to the holistic understanding of time, which allows to synthesize the essence and existence of human.

This article analyzes the understanding of time in the concept of the G.H. Mead. The G.H. Mead ontology is understood as the ontology of the process. Analysis of the modes of time leads the author to the conclusion that in the conception of the American pragmatist, eternity turns out to be opposed to time. Special attention is paid to the notion of emergence. According to G.H. Mead, it is emergence is the key to understanding all the modes of time. It was suggested about inadmissibility of opposition of modes of time with each other, and also the thought of inadmissibility derogatory attitude to any modus of time, or portions thereof. However, it is found out as far concept of the time of G.H. Mead can bring researchers to the holistic understanding of time, which allows to synthesize the essence and existence of human.
Шамша І. В. «Філософія теперішнього» Дж. Г. Міда як онтологія процесу / І. В. Шамша // Актуальні проблеми філософії та соціології: Науково-практичний журнал / Голов. ред. Д. В. Яковлев; відпов. секретар І. В. Шамша; Міністерство освіти і науки України; Національний університет "Одеська юридична академія". - Одеса, 2017. - Вип. 20. - С. 163-165.
Keywords: Дж. Г. Мід; розуміння часу; теперішнє; модуси часу; людина; Дж. Г. Мид; понимание времени; настоящее; модусы времени; человек; G.H. Mead; understanding of time; present; modes of time; human